'Awww, she is feeding you'. (31st August 2021) - Gan, Yumei
Abstract : Undertaking a video call with very young children can pose significant challenges, as children may wander away or fail to pay attention to the people on the screen. Previous studies have provided important insights into how adults try various strategies to engage young children in such video calls. Less attention has been paid, however, to the children's perspective: how children orient themselves toward video-mediated communication technologies and the nature of these mediated interactions. Based on 56 recorded hours of naturally occurring video calls between migrant parents and the very young children (aged 8–36 months) they leave behind in China, this article examines how these children spontaneously display engagement and disengagement during a video call. This study highlights children's interactional competence in engaging with the mediated format of interactions. Very young children can deploy various communicative resources that orient towards the affordance of video-mediated communication technology, such as manoeuvring the camera direction and initiating feeding and showing sequences. The analyses also illustrate that young children actively achieve disengagement in video calls through the artful use of language, body and the material world. These findings contribute to understanding children's situated practices with digital technology in family communication, and how children are active interlocutors who guide the adults' actions in moment-by-moment unfolding interactions.